Metal Complexes and Their Role in Treatment of the Arthritis - Ejaz Ali; Kanwal Ashiq; Manhaz Ghulam Nabi; Maria Gul; Mubashra Gul (Gazi Medical Journal)
Worldwide, rheumatoid arthritis is a major cause of morbidity and mortality. In recent years, the domain of inorganic medicinal chemistry has shown more interest in metal-based drugs owing to their beneficial pharmacological activities. Since then, many useful anti-cancer metal-based drugs have been introduced. However, less attention has been paid to improving inflammatory drugs based on metal complexes. The objective of this review is to recapitulate previously published studies that concentrated on metal-based drugs used for the treatment of arthritis. It is anticipated that the current compilation of earlier studies will be helpful for the researcher to find the data and areas for future studies. The literature survey was done without any time limit using the help of various electronic databases, including ScienceDirect, SpringerLink, Web of Science, PubMed, and the Cochrane Library. Articles published in the English language are used for the current review. Only 20 studies were found to be pertinent to the present review. Metal complexes of non-steroidal anti-inflammatory drugs have been the subject of extensive research. To date, metal complexes of drugs such as aspirin, ibuprofen, anthranilic acid, methotrexate, indomethacin, and aceclofenac have been studied and evaluated for their possible antiarthritic activity. Gold metal complexes showed better efficacy and have been used in clinical practice as well. Due to their advantageous therapeutic properties, metals and their complexes are becoming more and more important today. To find new treatments for diseases, it is suggested that the mechanism of action and potential toxicity of metal complexes must be assessed.